Comparison of active stretching technique and static stretching technique on hamstring flexibility - Meroni, R.; Cerri, G.; Lanzarini, C.; Barindelli, G.; della Morte, G.; Gessaga, V.; Cesana, G. C.; de Vito, G. (Clinical Journal of Sport Medicine, 2010)
The article presents a study that compares active and passive stretching techniques to identify the stretching technique to produce and maintain the best result in hamstring flexibility. The study conducted a randomized controlled trial among 65 volunteers who were divided into 2 groups that underwent active stretching exercises and passive stretching exercises. Results infer that active stretching technique can produce the greater gain in active knee extension range of motion (AKER) test.